Ragweed sublingual tablet immunotherapy: part II - practical considerations and pertinent issues - Pfaar, Oliver; Creticos, Peter Socrates (Immunotherapy, 2018)
Sublingual allergen immunotherapy (SLIT) has been demonstrated to be both efficacious and safe for the treatment of respiratory allergies such as allergic rhinoconjunctivitis or allergic asthma. Based on the clinical documentation of SLIT ragweed tablets, they have gained marketing authorization in the USA by the US FDA in 2014 for adult patients. Following clinical data from (pivotal) multicenter Phase II and III trials as performed in the USA and Canada and real life experience after registration in 2014, SLIT ragweed tablets can be recommended as efficacious and safe treatment option with disease modifying potential when adequately indicated and performed. Therefore, several practical issues should be considered for treating ragweed allergic patients with these tablets. This second part of a thorough review on ragweed SLIT tablets addresses important clinical questions which should be taken into account by the subscribing practitioner before initiation and during the treatment.
Gesehen am 23.08.2019